Branched endosomal disruptor (BEND) lipids mediate delivery of mRNA and CRISPR-Cas9 ribonucleoprotein complex for hepatic gene editing and T cell engineering - Marshall S. Padilla; Kaitlin Mrksich; Yiming Wang; Rebecca M. Haley; Jacqueline J. Li; Emily L. Han; Rakan El-Mayta; Emily H. Kim; Sofia Dias; Ningqiang Gong; Sridatta V. Teerdhala; Xuexiang Han; et al. (Nature Communications, 2025)
Abstract Lipid nanoparticles (LNPs) are the preeminent non-viral drug delivery vehicle for mRNA-based therapies. Immense effort has been placed on optimizing the ionizable lipid (IL) structure, which contains an amine core conjugated to lipid tails, as small molecular adjustments can result in substantial changes in the overall efficacy of the resulting LNPs. However, despite some advancements, a major barrier for LNP delivery is endosomal escape. Here, we develop a platform for synthesizing a class of branched ILs that improve endosomal escape. These compounds incorporate terminally branched groups that increase hepatic mRNA and ribonucleoprotein complex delivery and gene editing efficiency as well as T cell transfection compared to non-branched lipids. Through an array of complementary experiments, we determine that our lipid architecture induces greater endosomal penetration and disruption. This work provides a scheme to generate a class of ILs for both mRNA and protein delivery.